Addressing Cyberbullying among Junior High School Students: An In-Depth Examination of Prevalence, Impacts, and Preventive Strategies - Maranan, Mario; Kalalo, Albert; Lumbis, Amalia; Escueta, Jocelyn (JPAIR Multidisciplinary Research, 2025)
The purpose of the study is to examine how respondents see various social media platforms as typical venues for cyberbullying to develop a program that will lessen or eliminate cyberbullying experiences among junior high school students. The study tackles the need to comprehend the frequency and effects of cyberbullying on particular social media platforms, offering insightful information about the specific types of online bullying that children encounter. The majority of respondents were in Grade 10.  Despite the reduced prevalence, cyberbullying still significantly affects students' well-being in terms of problems, self-esteem issues and social anxiety. Verbal harassment and stalking were the forms of online bullying experienced by the respondents; other types of bullying were relatively rare overall. Respondents also mentioned infrequent consequences resulting from their encounters with cyberbullying, such as sleep disturbances, social anxiety and low self-esteem. These findings highlight the nature of cyberbullying and its potential adverse effects on students' social connections, academic performance and overall well-being. While cyberbullying is not common, it affects students' mental well-being, especially in terms of behavioral issues, low self-esteem, and social anxiety. Thus, to tackle cyberbullying, parents, schools, and other institutions should offer educators and children guidelines, educational initiatives, and assistance.
Keywords: cyberbullying; social media; Junior High School learners; educational settings; educational initiatives; descriptive; Philippines